Slovenske znanstvene revije v letu 2021 - Pogačnik, Aleš (Organizacija znanja, 2022)
Based on (1) the lists of Slovenian scientific journals in international databases used to evaluate publications by Slovenian researchers, (2) regular government calls for support of scientific journals, and (3) a more detailed review of the main international bibliographic databases for this system (SNIP, JCR, SJR), we can conclude that 219 Slovenian journals with scientific articles were published in 2021. Every second journal was founded after 1990, and about 60% of them belong to social sciences and humanities. Their publishers are Slovenian institutions and the journals are diamond journals: only 7.7% of journals are affiliated with major global publishers and only 3.7% use APC (Article Processing Charge). The vast majority (about 90%) of journals claim that they publish their content in open access. More than half of the journals on domestic websites or in national repositories dLib (Digital Library of Slovenia) and DiRROS (Digital Repository of Research Organizations of Slovenia) have free access to a complete archive. Half of them use Creative Commons licenses, about the same number of them (mostly the same journals) also use DOI (Digital Object Identifier), one third of journals use OJS (Open Journal System) and a handful (4.1%) also publish in one of the XML formats. Most journals started publishing in Slovenian, but today articles in almost three quarters of the journals can also be published in English. Technically, they are still below the world average, which is at least partly due to two systemic anomalies: stable and well-organized funding of the domestic scientific press has stagnated for several years and the Slovenian science evaluation system encourages publication in foreign journals.
Keywords: bibliometrics; bibliometrija; odprta znanost; open science; periodicals; periodične publikacije; scientific press; Slovenia; Slovenija; znanstveni tisk